Museums and the Promotion of African Indigenous Religion in Yorubaland, Nigeria - Oyewole, Ogunbiyi Olatunde (KWASU Journal of Religious Studies, 2018)
Museums are edifices meant for the collection of antiquities or relics of creativity, knowledge and culture, ensuring that these collections exist for future generations. They provide treatment and preventive care for rare and valuable artistic collections of high value. African Religion is an expressive religion that has sought over the years to express her religious experience through the medium of arts and crafts. One of the ethnic groups among the Africans whose religion has gone all over the world is the Yoruba. Their dominant religious expressions have produced several arts and crafts that have emerged along with others in various museums of the world. This paper, in its purpose has three main objectives: to examine the role of museums in promoting the documentation and dissemination of African Indigenous Religion, to evaluate the efforts of the museum association in the documentation, preservation and dissemination of information about African Religion and to create a general awareness of the need for the public to have access to information on the religion of their forefathers as contained in museum citadels. The historical method was used in the elucidation of this enterprise. The researcher also visited various museums in Southwest Nigeria for on the spot assessment and interviews. The paper concludes on the note that the museums of Southwestern Nigeria are trying to preserve the religious arts of the Yoruba people but the buildings need much to be desired. Consequently, they are not able to perform the role expected of them properly. It was recommended that private institutions should partner with these government enterprises to ensure that these enigmatic heritages are preserved for generations to learn.